The phenomenon of body in the postmodern conceptions: the historical dimension of problem - Yaroslav Рotapenko (Cхід, 2013)
The historical consideration of analysis of bodiness in postmodern discourse are lead. The special attention are given to the constructivistic, deconstructivistic and semiotic and textual approaches.